3D printed semi-solid zinc-manganese battery. (2022) - Li, Xue Liang; Yang, Hui Ying
Abstract: The fabrication and assembly of electrodes is very important for the manufacture of batteries. Here, we demonstrate a 3D printing technique for the construction of functional electrodes (including anode, cathode, and semi-solid electrolyte) for zinc-manganese batteries. The printed anode consists of many zinc microspheres, which allow for a high degree of zinc utilization. The printed cathode has a layered porous structure with a high surface area, giving the electrode surface activity and a fast diffusion channel for the electrochemical reaction. The printed semi-solid electrolyte has designed ion channels that facilitate rapid ion transport. Benefiting from these advantages, the assembled zinc-manganese ion battery achieves high energy density and better cycling performance (without zinc dendrites). The reasons behind these properties and their respective characteristics are well explored and clarified. This work smartly combines direct ink writing technology and light-curing printing technology to achieve the first fully 3D printed battery, which could revolutionize battery manufacturing in the future.